ATTENDANCE OF PREMATURE NEWBORN BABIES FROM THE BREASTFEEDING CLINIC OF HUMAN MILK BANK - Maria Celestina Bonzanini Grazziotin; Inês Sayuri Yamasaki (Universidade Federal do Paraná, 2000)
This study aims to identify whether premature newborn babies present weight gain according to normal breastfeeding standards, upon counselling of mother by the nursing team of Human-Milk Bank. We watched 300 couples - mothers and their premature babies in the 1999. The outcome showed that the majority of babies gained weight right after the first counselling by the nursing team, and that the mothers showed greater ability and confidence in breastfeeding management. This study also shows the importance of continuous attendance to the mothers by competent nursing team after hospital discharge.